Photoplethysmographic heart rate and blood pressure estimation in dynamic condition - Zazula, Damjan (LAHA (Online ed.), 2014)
This paper describes a novel, unobtrusive photoplethysmographic device and experiments conducted in a dynamic condition. The device complements a photoplethysmograph with a dynamometer, an accelerometer, and a thermometer. We built it in the door handle of a refrigerator and made tests during the door opening and closing. Short-term PPG signals were obtained across all fingers pulling the handle. In parallel, we measured the standard ECG lead II as a reference for the detected heartbeat verification. The blood pressure of each participant was registered before each experimental trial by a standard sphygmomanometer. Based on the PPG signals, we ran our computer algorithms for detecting the heartbeats and estimating the mean blood pressure. Satisfactory results were achieved for heartbeats, with 97.62% sensitivity and 90.31% precision. However, blood pressure estimation appeared to be not very efficient - neither linear nor exponential modeling could lower the estimated mean absolute error in comparison to referential mean blood pressures below 6 mmHg
Keywords: blood pressure estimation; heartbeat detection; krvni tlak; photoplethysmography in dynamic condition; senzorji; srčni utrip; unobtrusive sensors